Understanding Patterns of Economic Insecurity for Post-Soviet Migrant Women in Europe - Gewinner, Irina; Salvino, Stefania (Frontiers in Sociology, 2021)
This study deals with meanings of economic insecurity for post-Soviet migrant women in Germany, Italy, and Spain, elaborating on its cultural underpinnings. Drawing upon several data sources, including interviews, observation, and online data, as well as judicial material, this study addresses the ways women from the former Soviet Union experience economic insecurity and which strategies they develop to cope. We consider women’s age, social background, and level of education, analysing their embeddedness into different life domains. We identify four patterns of coping with economic insecurity, linked to individual characteristics, cultural values and legal frame conditions in the countries under investigation, and provide implications for social mobility and conservative backlash in Europe.